PENERAPAN ALGORITMA C4.5 UNTUK MEMPREDIKSI BENCANA GUNUNG MELETUS DI INDONESIA - Ratih Nurdiyani Sari; Novrina, Novrina; Syarifah Azharina S (Jurnal Teknik dan Science, 2024)
This research aims to predict one of the natural disasters in Indonesia, namely Mount Eruption. This natural disaster occurs quite often in Indonesia and results in losses for residents around active volcanoes. Based on this, the research team wants to create a decision tree that can help predict the situation before a volcano erupts, which can later be applied so that residents around active volcanoes and ordinary people can know the signs before a volcanic eruption occurs. This research will use the application of data mining with the c4.5 algorithm method as a tool in creating decision trees.